Characterizing Non-ideal Impacts of Reconfigurable Hardware Workloads on Ring Oscillator-Based Thermometers - Sayed, M. A.; Jones, P. H. (2011 International Conference on Reconfigurable Computing and FPGAs, 2011)
Thermal issues have resulted in growing concerns among industries fabricating various types of devices, such as Chip Multiprocessors (CMP) and reconfigurable hardware devices. Since passive cooling costs have risen considerably and packaging for worst-case is no longer practical, dynamic thermal management techniques are being devised to combat thermal effects. For such techniques to be applied effectively, it is necessary to accurately measure device temperatures at run time. Although several techniques have been proposed to measure the on-chip temperatures of reconfigurable devices, ring oscillators in many ways are a preferred choice due to their strong linear temperature-dependence and compact design using available spare reconfigurable resources. A major problem in using ring-oscillators to measure temperature, however, is their strong dependence on the core voltage of, and current distribution throughout the device under test. One of the reasons for variations in these properties is changes in the workload running on the device. Researchers have seen large shifts in the output frequencies of ring-oscillators due to core voltage swings on reconfigurable devices, and have tried to find alternate ways of measuring temperature that attempt to mitigate these effects. The need, however, is to have a workload-compensated ring oscillator-based thermometer for reconfigurable devices. To obtain this, it is first necessary to characterize the non-ideal effects of workload variations on ring oscillator response. Where non-ideal refers to impacts on ring oscillator oscillation frequency due to phenomena other than the workload's impact on device temperature. This paper performs such a characterization, in which the effects of workload variation on ring oscillator output frequency is quantified. A complete hardware-software setup is designed to collect temperature and power related data along with ring oscillator response to varying workload configurations. In addition, a potential issue with using the Xilinx System Monitor to measure die temperature at high ranges is also briefly discussed.